Supramolecular Rotaxane‐Based Multi‐Modal Probes for Cancer Biomarker Imaging. Issue 29 (20th May 2022) - d'Orchymont, Faustine; Holland, Jason P.
Abstract: Mechanically interlocked molecules present opportunities to construct therapeutic drugs and diagnostic imaging agents but harnessing supramolecular chemistry to make biologically active probes in water is a challenge. Here, we describe a rotaxane‐based approach to synthesise radiolabelled proteins and peptides for molecular imaging of cancer biomarkers in vivo. Host–guest chemistry using β‐cyclodextrin‐ and cucurbit[6]uril‐catalysed cooperative capture synthesis produced gallium‐68 or zirconium‐89 radiolabelled metallo[4]rotaxanes. Photochemical conjugation to trastuzumab led to a viable positron emission tomography (PET) radiotracer. The rotaxane architecture can be tuned to accommodate different radiometal ion complexes, other protein‐ or peptide‐based drugs, and fluorophores for optical detection. This technology provides a platform to explore how mechanical bonding can improve drug delivery, enhance tumour specificity, control radiotracer pharmacokinetics, and reduce dosimetry. Abstract : A rotaxane‐based platform is introduced for the design of multi‐modality molecular imaging probes. Cooperative capture synthesis with architectural control is used to make viable cancer‐specific imaging agents based on molecularly interlocked rotaxanes that feature radiometal ion complexes for positron emission tomography imaging, fluorescent probes for optical detection, and small‐molecules or monoclonal antibodies for tumour targeting.